A new method for depth of interaction determination in PET detectors. (1st June 2016) - Pizzichemi, M; Stringhini, G; Niknejad, T; Liu, Z; Lecoq, P; Tavernier, S; Varela, J; Paganoni, M; Auffray, E
Abstract: A new method for obtaining depth of interaction (DOI) information in PET detectors is presented in this study, based on sharing and redirection of scintillation light among multiple detectors, together with attenuation of light over the length of the crystals. The aim is to obtain continuous DOI encoding with single side readout, and at the same time without the need for one-to-one coupling between scintillators and detectors, allowing the development of a PET scanner with good spatial, energy and timing resolutions while keeping the complexity of the system low. A prototype module has been produced and characterized to test the proposed method, coupling a LYSO scintillator matrix to a commercial SiPMs array. Excellent crystal separation is obtained for all the scintillators in the array, light loss due to depolishing is found to be negligible, energy resolution is shown to be on average 12.7% FWHM. The mean DOI resolution achieved is 4.1 mm FWHM on a 15 mm long crystal and preliminary coincidence time resolution was estimated in 353 ps FWHM.